Strain Mapping and Raman Spectroscopy of Bent GaP and GaAs Nanowires - Im, Hyung Soon; Park, Kidong; Kim, Jundong; Kim, Doyeon; Lee, Jinha; Lee, Jung Ah; Park, Jeunghee; Ahn, Jae-Pyoung (AMER CHEMICAL SOC, 2018)
Strain engineering of nanowires (NWs) has been recognized as a powerful strategy for tuning the optical and electronic properties of nanoscale semiconductors. Therefore, the characterization of the strains with nanometer-scale spatial resolution is of great importance for various promising applications. In the present work, we synthesized single-crystalline zinc blende phase GaP and GaAs NWs using the chemical vapor transport method and visualized their bending strains (up to 3%) with high precision using the nanobeam electron diffraction technique. The strain mapping at all crystallographic axes revealed that (i) maximum strain exists along the growth direction ([111]) with the tensile and compressive strains at the outer and inner parts, respectively; (ii) the opposite strains appeared along the perpendicular direction ([(2) over bar 11]); and (iii) the tensile strain was larger than the coexisting compressive strain at all axes. The Raman spectrum collected for individual bent NWs showed the peak broadening and red shift of the transverse optical modes that were well-correlated with the strain maps. These results are consistent with the larger mechanical modulus of GaP than that of GaAs. Our work provides new insight into the bending strain of III-V semiconductors, which is of paramount importance in the performance of flexible or bendable electronics.
Keywords: SEMICONDUCTOR NANOWIRES; ELECTRON-DIFFRACTION; GERMANIUM NANOWIRES; OPTICAL-PROPERTIES; LIGHT-EMISSION; TENSILE; PARAMETERS